The Bathonian and Callovian of the Northwest-Iberian Range: Stages of facial paleogeographical differentiation on an epicontinental platform. - Wilde, S. (Cuadernos de Geología Ibérica, 1990)
The Bathonian and Callovian stages of the NW-Iberian Range. which formations are newly defined, correspond approximately to two «macrosequences» limited by wide-spread uncorformity horizons. During this time the facial environmental conditions of this epicontinental shallowmarine depositional realm led into an obviously intensified regional differentiation. This is resulted by increasing tectonic activities causing a structural paleogeographical framework with very variable subsidences, supposingly in connection with the initial Biscay spreading phase.